2022
DOI: 10.3389/fimmu.2022.930397
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Lipocalin 10 Exacerbates Diabetes-Induced Cardiomyopathy via Disruption of Nr4a1-Mediated Anti-Inflammatory Response in Macrophages

Abstract: Metabolic disorders (i.e., hyperglycemia, hyperlipidemia, and hyperinsulinemia) cause increased secretion of inflammatory cytokines/chemokines, leading to gradual loss of cardiac resident macrophage population and increased accumulation of inflammatory monocytes/macrophages in the heart. Such self-perpetuating effect may contribute to the development of cardiomyopathy during diabetes. Recent meta-analysis data reveal that lipocalin 10 (Lcn10) is significantly downregulated in cardiac tissue of patients with he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Currently, it is well appreciated that neutrophils and monocytes/macrophages with pro-inflammatory phenotypes are typically recruited to I/R hearts ( 5 , 6 ). Therefore, according to previous reports ( 28 , 29 , 41 , 42 ), we characterized cardiac neutrophils as CD45 + Ly6G + cells, cardiac macrophages as CD45 + Ly6G – CD11b + F4/80 + Ly6C lo , and cardiac monocytes as CD45 + Ly6G – CD11b + F4/80 + Ly6C hi , and the gating strategy is shown in Supplemental Figure 6 . Please note that total number of CD45 + cells was significantly increased by 1.5-fold in KO mCherry hearts at the time point of 7 days post-I/R, compared with control WT mCherry groups ( Supplemental Figure 7 , A and B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, it is well appreciated that neutrophils and monocytes/macrophages with pro-inflammatory phenotypes are typically recruited to I/R hearts ( 5 , 6 ). Therefore, according to previous reports ( 28 , 29 , 41 , 42 ), we characterized cardiac neutrophils as CD45 + Ly6G + cells, cardiac macrophages as CD45 + Ly6G – CD11b + F4/80 + Ly6C lo , and cardiac monocytes as CD45 + Ly6G – CD11b + F4/80 + Ly6C hi , and the gating strategy is shown in Supplemental Figure 6 . Please note that total number of CD45 + cells was significantly increased by 1.5-fold in KO mCherry hearts at the time point of 7 days post-I/R, compared with control WT mCherry groups ( Supplemental Figure 7 , A and B).…”
Section: Resultsmentioning
confidence: 99%
“…Isolation, culture, and treatment of BMDMs. BMDMs were isolated and cultured as we described previously (41). Briefly, WT, Sectm1a-KO, or Gitr-KO mice were euthanized as above, followed by the removal of both hind legs.…”
Section: Methodsmentioning
confidence: 99%
“…[181], FLT1 [182], ABCA3 [183], DUOX1 [184], KL (klotho) [185], ALOX5AP [186], FPR2 [187], IL27 [188], FZD4 [189], MPO (myeloperoxidase) [190], CTSD (cathepsin D) ABCA3 [636], KL (klotho) [637], PLK1 [638], GAPDH (glyceraldehyde-3phosphate dehydrogenase) [639], MPO (myeloperoxidase) [640], LPL (lipoprotein lipase) [641], TLR8 [642], MUC1 [643], FOXF1 [644], VCAN (versican) [645] and FDPS (farnesyl diphosphate synthase) [646] have been proposed as the most promising biomarkers for pulmonary hypertension. PTGS2 [647], NR4A1 [648], IL6 [649], CXCL8 [650], CD69 [651], CXCL1 [652], SOCS2 [653], SOCS3 [654], CCL3 [655], CCL5 [656], VCAM1 [657], CCL2 [658], CXCL5 [659], DUSP5 [660], CXCL12 [661], KLF10 [662], KLK5 [663], CD3E [664], CD3D [665], IL1B [666], AREG (amphiregulin) [667], SERPINE1 [668], OSM ( [682], BMP2 [683], LDLR (low density lipoprotein receptor) [684], CDKN1A [685], RGS16 [686], TNFAIP3 [687], BMP4 [688], ICAM1…”
Section: Discussionmentioning
confidence: 99%
“…Under conditions of increased ROS and reduced bioavailable NO, these macrophages can polarize into a pro-inflammatory M1 phenotype ( 54 56 ). Recent studies have observed an upregulation of pro-inflammatory M1 polarization in diabetic cardiac tissue, while the M2 anti-inflammatory response is suppressed ( 57 61 ).…”
Section: Pathogenesis Of Dcmmentioning
confidence: 99%